ENVELHECIMENTO ACELERADO DE SEMENTES DE PINHÃO-MANSO - Márcio Dias Pereira (Pesquisa Agropecuária Tropical, 2012)
Jatropha curcas L. is an oleaginous plant that has distinguished itself by presenting the qualities necessary to the biodiesel production. This study aimed to adjust the accelerated aging test methodology to evaluate the physiological potential of Jatropha curcas seeds. For this, four seeds lots were initially characterized by water content, germination percentage and first counting, seedlings emergence percentage and speed index, low temperature germination, and shoot height. The treatments included three temperatures (41ºC, 42ºC, and 45ºC) and four seeds exposure times (24, 48, 72, and 96 hours), in about 100% relative humidity. The accelerated aging test carried out for 24 hours, at 41ºC, was efficient for evaluating the Jatropha curcas vigour seeds, allowing to classify lots according to vigour levels, similarly to the germination first counting tests, seedlings emergence, low temperature germination, emergence speed index, and shoots height.